‘Can't see the forest for the trees’: The importance of fungi in the context of UK tree planting - Aileen Baird; Francis Pope (Food and Energy Security, 2022)
Abstract Tree planting now forms a major part of the UK climate mitigation strategy, with targets to increase the forest cover from the current 13% to 17%–20% by 2050. A tree planting strategy on this scale requires a significant amount of planning, bringing together expertise from a wide range of practitioners. We highlight four key reasons why fungi should be considered in tree planting strategies: 1. Fungi can cause severe tree disease. 2. Fungi can cause significant human health burdens. 3. Forest soil carbon and nutrient cycling is controlled by fungi. 4. Climate change is already affecting fungi. Following from these four reasons, we explore the ways in which the negative effects of fungi, such as plant and human disease, can be mitigated against, whilst also protecting and promoting the benefits of fungi in carbon storage and biodiversity. Based on this, we outline seven guidelines which should be integrated into existing tree planting guidelines and UK policy: A. Monitor tree fungal disease emergence and spread, including in source material trade (e.g. seeds and saplings). B. Choose tree species combinations appropriate to the specific habitat and appropriate for biodiversity and carbon storage goals. C. Develop and implement a widely accessible fungal spore forecast to complement existing pollen forecasts. D. Protect existing ancient and mature woodlands. E. Promote planting on suitable land types, avoiding grasslands and wetlands. F. Assess proposed and existing forest sites, ideally using a combination of fungal fruit body surveys and eDNA techniques. G. Develop and implement the UK Fungi Red List into UK law.